Enhancing Writing Skills through English Short Story Creation among Tenth-Grade Students at High School - Sartikawati, Dewi; Wahab, Abdul; Hendriani, Ria (Universitas Qamarul Huda Badaruddin, 2025)
This research examines the effectiveness of English short story creation as a method to enhance students’ writing skills. Conducted at MA Al-Ma’arif Bonder with a sample of 16 tenth-grade students, the research employed a pre-experimental one-group pre-test and post-test design. Writing skills were assessed based on five aspects: ideas/content, structure, vocabulary, grammar, and mechanics. Data were analyzed using descriptive statistics and a paired sample t-test with SPSS 25. Results revealed significant improvement in students’ writing performance, with the mean score increasing from 56.8 in the pre-test to 75.3 in the post-test. The paired sample t-test produced a significance value of 0.000, indicating a positive effect of short story writing on students’ writing proficiency. This suggests that integrating creative writing activities into English instruction can foster students’ language development, motivation, and creativity.